2007
DOI: 10.1158/1078-0432.ccr-07-1057
|View full text |Cite
|
Sign up to set email alerts
|

Binding Activities and Antitumor Properties of a New Mouse/Human Chimeric Antibody Specific for GD2 Ganglioside Antigen

Abstract: Purpose: We previously generated a mouse monoclonal antibody (mAb) specific for the tumorassociated GD2 ganglioside antigen. Here, we describe the development of a chimeric anti-GD2 mAb for more effective tumor immunotherapy. Experimental Design: We cloned the cDNA encoding the immunoglobulin light and heavy chains of the 60C3 anti-GD2 mAb, and constructed chimeric genes by linking the cDNA fragments of the variable regions of the murine light and heavy chains to cDNA fragments of the human n and g1constant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…We were, however, unable to detect apoptosis after tumor cells treatment with either ch14.18 or c.8B6 mAbs in our experiments. The loss of pro-apoptotic activity upon chimerization of mouse mAb 60C3 specific for GD2 ganglioside was also observed previously [17]. Although the cell death mechanism initiated by the mouse mAb 8B6 have not been yet elucidated, our results suggest that the pro-apoptotic activity of anti-GD2 and anti-OAcGD2 mAbs can not fully explained by their sole antigen recognition activity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We were, however, unable to detect apoptosis after tumor cells treatment with either ch14.18 or c.8B6 mAbs in our experiments. The loss of pro-apoptotic activity upon chimerization of mouse mAb 60C3 specific for GD2 ganglioside was also observed previously [17]. Although the cell death mechanism initiated by the mouse mAb 8B6 have not been yet elucidated, our results suggest that the pro-apoptotic activity of anti-GD2 and anti-OAcGD2 mAbs can not fully explained by their sole antigen recognition activity.…”
Section: Discussionsupporting
confidence: 83%
“…Chimeric anti-OAcGD2 mAb c.8B6 was constructed by joining the complementary deoxyribonucleic acid for the variable region of the murine antibody 8B6 [11] with the human constant regions of the γ1 heavy chain and the κ light chain. The light and heavy chain expression vectors for chimeric antibody were constructed using the same method as described in a previous report [17]. Appropriate light and heavy expression vectors were co-transfected into Chinese hamster ovary (CHO-S) cells and stable transfectants were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with this earlier study, we did see a slight cross-reactivity of mAb 14G2a against O AcGD2 in immuno-TLC experiments (data not shown). Scatchard analysis further showed that mAb 8B6 and mAb 14G2a displayed equivalent binding affinities for their respective epitopes that were within the range anti-GD2 antibodies [21], [24], [31], [32]. O AcGD2 expression was confirmed on all of the 12 neuroblastoma tumor sections tested.…”
Section: Discussionmentioning
confidence: 94%
“…Since in vitro cell culture experiments have shown that various anti-GD2 mAbs inhibit tumor cell growth by directly inducing apoptosis [8], [21], [22], we studied whether the mAb 8B6 displayed the same effects on tumor cell viability. To test for the antitumor activity of mAb 8B6, we choose the EL4 cell line because it is tumorigenic in syngeneic immunocompetent C57Bl/6 mice and because it was used previously in many preclinical studies with anti-GD2 mAbs [23].…”
Section: Resultsmentioning
confidence: 99%
“…Among numerous anti-carbohydrate mAbs raised against malignant tumor tissues, several reportedly kill targeted cells through antibody-dependent cellular cytotoxicity and antibody-dependent phagocytosis by macrophages (1720). The mAb F77, which was produced by immunizing mice with the prostate cancer cell line PC-3 (20), is one such cytotoxic antibody.…”
Section: Introductionmentioning
confidence: 99%